1999
DOI: 10.1002/(sici)1097-0010(19990701)79:9<1183::aid-jsfa341>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental stress during tuber development on accumulation of glycoalkaloids in potato (Solanum tuberosum L)

Abstract: The effects of low temperature and of combined stresses, cool temperature and waterlogging and also warm temperature and drought, on potato tuber glycoalkaloid levels were investigated, with emphasis on comparison of tubers of similar size. The early maturing cultivars Home Guard, Rocket and British Queen were grown under favourable controlled environment conditions (18/14°C day/night temperature, 14 h photoperiod) until the imposition of treatments after the start of tuber initiation. Transfer to low temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…However, extreme temperature data show larger differences for 2010 than for 2011, which may partially explain the differences observed. Responses of glycoalkaloid levels in tubers to environmental effects seem to be variable depending on the variety, with some varieties showing differences in stressed conditions while others do not seem to be affected (Papathanasiou and others ; Bejarano and others ). Studies in controlled growing environments have found that heat stress increase the glycoalkaloid content, with diverse results reported for low temperatures (Nitithamyong and others ; Papathanasiou and others ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extreme temperature data show larger differences for 2010 than for 2011, which may partially explain the differences observed. Responses of glycoalkaloid levels in tubers to environmental effects seem to be variable depending on the variety, with some varieties showing differences in stressed conditions while others do not seem to be affected (Papathanasiou and others ; Bejarano and others ). Studies in controlled growing environments have found that heat stress increase the glycoalkaloid content, with diverse results reported for low temperatures (Nitithamyong and others ; Papathanasiou and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Responses of glycoalkaloid levels in tubers to environmental effects seem to be variable depending on the variety, with some varieties showing differences in stressed conditions while others do not seem to be affected (Papathanasiou and others ; Bejarano and others ). Studies in controlled growing environments have found that heat stress increase the glycoalkaloid content, with diverse results reported for low temperatures (Nitithamyong and others ; Papathanasiou and others ). Drought stress seems to increase the glycoalkaloid content as well, but excess of water has the same effect at low temperatures during later stages of development only (Papathanasiou and others ; Bejarano and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Papathanasiou et al (1999) reported that heat stress increases the glycoalkaloid content, with various results reported for low temperatures. Drought stress seems to increase the GA content as well, whereas the excess of water has the same effect only at low temperatures during later stages of development (Papathanasiou et al 1999, Bejarano et al 2000. Cold and wet periods during summer were also associated with higher levels of glycoalkaloids (Haase 2010, Valcarcel et al 2014).…”
Section: Glycoalkaloids Contentmentioning
confidence: 91%
“…It is difficult to determine the exact causes of increased GA accumulation in tubers, but many authors agree that the synthesis of GA is related to stress in general, during both growth and storage (Petersson et al 2013, Valcarcel et al 2014, Mekapogu et al 2016. Papathanasiou et al (1999) reported that heat stress increases the glycoalkaloid content, with various results reported for low temperatures. Drought stress seems to increase the GA content as well, whereas the excess of water has the same effect only at low temperatures during later stages of development (Papathanasiou et al 1999, Bejarano et al 2000.…”
Section: Glycoalkaloids Contentmentioning
confidence: 99%
“…In contrast, effects of water stress on radiation use efficiency, harvest index and tuber dry matter concentration (Schittenhelma et al 2005) and on nitrate reductase (Foyer et al 1998;Chandra et al 2004;Das et al 2005;Kar et al 2005;Xu and Guang 2006) are relatively small. Water deficit also increases reducing sugar concentration in the tuber, tuber cracking and malformation, surface abrasions, hollow heart, brown centre, internal brown spot, vascular discolouration or bruising, starch degradation in the tuber stem end and total glycoalkaloid concentration (Papathanasiou et al 1999). Reflectance indices were used to measure biomass and drought stress, changes in leaf water content (Francois and De Proft 2005) and water stress (Bahrun et al 2003).…”
mentioning
confidence: 99%